Do men and women use similar adaptive locomotion to clear static and dynamic obstacles? - Gobbi, Lilian [UNESP]; Da Silva, Jean [UNESP]; Barbieri, Fabio [UNESP] (Termedia Sp. z.o.o., 2011)
Purpose. The purpose of this study was to analyze the influence of gender on the adaptive locomotion in the clearance of obstacles. Specifically, it was evaluated if there are differences in the space-temporal parameters between male and female in the clearance of and dynamic obstacles moving at both slow and fast speeds. Basic procedures. Five young male adults and five young female adults took part in this study. The task was performed in three conditions: static obstacle and dynamic obstacle - clearance perpendicular to the participant's trajectory at slow speed (1.07 m/s) and at fast speed (1.71 m/s). The trials were recorded by two digital cameras and spatial-temporal information was obtained. Main findings. The dynamic obstacle conditions required more visual inspection. The results showed different adaptive locomotion between the sexes. The distinct gait patterns were evidenced for the spatial and temporal variables and cadence in the three conditions. Conclusions. The women presented a more conservative behavior, which was evidenced by the increase of the length in the penultimate step and in the toe clearance.
Keywords: adaptive locomotion; dynamic obstacle; gender